A COMUNICAÇÃO VIA INTERNET NA INCLUSÃO E INTEGRAÇÃO DE DEFICIENTES AUDITIVOS: um estudo sobre a região do ABC / SP - Carmo Neto, Honório do (2007)
The objective of this work is to understand how the communication, through the Internet, is used and built, considered the subjects of inclusion and integration of hearing deficiency people. The concepts about communication, inclusion and integration are analyzed; the hearing deficiency and its meaning for the individuals and the subject of the sites in the Internet that deals with this subject and the type of approach communicational used inside this universe are also analyzed. The message of the transmitter (via internet) - decoded by the receiver (hearing deficient) - supplies to the receiver an integration in the world mediation capable to supply an appropriate inclusion and to facilitated the use of Internet for the hearing deficient (receiver). The analysis of the answers of the applied questionnaires to the users and the transmitters of information of the sites, as well as the used theories, should show if there are difficulties in the construction of new messages in the field of Internet and in the use of the receivers. The way for inclusion and communicational integration will go through the transformation of those messages and for projects and actions to be developed in the construction of the sites in the Internet.(AU)